The Effects of Immigration in a Developing Country: Brazil in the Age of Mass Migration - David Escamilla-Guerrero; Andrea Papadia; Ariell Zimran (Institute of Labor Economics (IZA), 2024)
The effects of immigration are reasonably well understood in developed countries, but they are far more poorly understood in developing ones despite the importance of these countries as immigrant destinations. We address this shortcoming by studying the effects of immigration to Brazil during the Age of Mass Migration on its agricultural sector in 1920. This context benefits from the widely recognized value of historical perspective in studies of the effects of immigration. But unlike studies that focus on the United States to understand the effects of migration from poor to rich countries, our context is informative of developing countries' experience because Brazil in this period was unique among major migrant destinations as a low-income country with a large agricultural sector and weak institutions. Instrumenting for a municipality's immigrant share using the interaction of aggregate immigrant inflows and the expansion of Brazil's railway network, we find that a greater immigrant share in a municipality led to an increase in farm values. We show that the bulk of the effect of immigration can be explained by more intense cultivation of land, which we attribute to temporary immigrants exerting greater labor effort than natives. Finally, we find that it is unlikely that immigration's effect on agriculture slowed Brazil's structural transformation.
Keywords: F22; J61; N36; N56; O13; O15; Q15; 330; immigration; developing countries; effects of immigration; age of mass migration; Brazil; agriculture